Should knowledge of classical dance be essential for medical practitioners? - Narayan, Shovana T (Research and Humanities in Medical Education, 2014)
The medical field is constantly throwing challenges, leading to considerable stress for its practitioners. Medical practitioners are expected to be professional, have up-to-date knowledge and expertise, and the ability to withstand fatigue. Through it all they are expected to remain motivated, respectful and humane, patient and kind, and confident and sensitive. The author demonstrates how learning dance can stimulate creativity, increase motivation and bolster social intelligence in medical practitioners.